2018
DOI: 10.1177/1468087418768117
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of diesel engine cylinder deactivation transition strategies

Abstract: Cylinder deactivation is an effective strategy to improve diesel engine fuel efficiency and aftertreatment thermal management when implemented through deactivation of both fueling and valve motion for a set of cylinders. Brake power is maintained by injecting additional fuel into the remaining activated cylinders. The initial deactivation of cylinders can be accomplished in various ways, the two most common options being to trap freshly inducted charge in the deactivated cylinders or to trap combusted gases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…The charge trapping and release strategies implemented during deactivation and reactivation of cylinders have a significant impact on the brake thermal efficiency of the engine. Options include fresh charge trapping (deactivation of a cylinder after its intake event 16,18,19,2225 ), combusted charge trapping (deactivation of a cylinder after fuel injection 1,18,19,25 ), and low-pressure charge trapping (deactivation of a cylinder after its exhaust event 16,18,19 ). CDA can be implemented using either fresh charge or combusted charge trapping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge trapping and release strategies implemented during deactivation and reactivation of cylinders have a significant impact on the brake thermal efficiency of the engine. Options include fresh charge trapping (deactivation of a cylinder after its intake event 16,18,19,2225 ), combusted charge trapping (deactivation of a cylinder after fuel injection 1,18,19,25 ), and low-pressure charge trapping (deactivation of a cylinder after its exhaust event 16,18,19 ). CDA can be implemented using either fresh charge or combusted charge trapping.…”
Section: Methodsmentioning
confidence: 99%
“…Rebbert et al 23 advise trapping higher pressure exhaust gas, either by fresh charge trapping or by combusted charge trapping, in the cylinder to reduce oil consumption. Allen et al 25 performed a comparative analysis of fresh charge trapping and combusted charge trapping strategies on a diesel engine during fixed CDA and found that the pressure of the trapped charge in the deactivated cylinders decayed quite rapidly due to heat and mass loss via gas blowby.…”
Section: Methodsmentioning
confidence: 99%
“…al. 1 . Images captured of combustion events immediately following reactivation of the VDE cylinder, i.e.…”
Section: Image Analysis Of Vde Eventsmentioning
confidence: 99%
“…al. 1 found out in their study that due to blow-by around the piston rings and heat loss through cylinder walls, cylinder pressures for combusted charge and fresh charge converge within a second. Therefore, the performance difference of trapping combusted charge or fresh charge is negligible.…”
Section: Introductionmentioning
confidence: 96%
“…Usually, exactly half of the number of cylinders are disabled in the deactivated mode [5][6][7]. More recently, however, there have been new concept proposals aiming at deactivating only one cylinder of a multi-cylinder engine [8][9][10].…”
Section: Introductionmentioning
confidence: 99%